Fatherless children and listening spirits: measuring kinship in ritual in northern Laos - Stolz, Rosalie (Social analysis, 2021)
Kinship among Khmu villagers of northern Laos is usually presented in anthropology as patrilineal. However, the ritual of a ‘small marriage’ can confirm a child’s belonging to the mothers’ house. The affirmation of the child’s maternal belonging is simultaneously about separation and exclusion from paternal ties and requires for its success careful measurements of kinship. During the ritual, quantities of food, gifts, and money become indicators of belonging. Human measurements are accompanied by spirit measurements that are unknowable but can have fatal consequences. Even though rituals are meant to achieve closure and establish belonging, ambiguities remain as a result of diverging measurements of kinship.